DIPPENAAR, JG Inventory of documents - DIPPENAAR, DIPPENAAR (ARCA, 2018)
Photographs of Pres. Paul Kruger, Genl. CR de Wet and Genl. Manie Maritz
Photographs
Keywords: DIPPENAAR, JG; Photographs; Pres. Paul Kruger; Genl. CR de Wet; Genl. Manie Maritz